ENCEPHALOPATY AKUT PADA ANAK DENGAN KELAINAN METABOLISME BAWAAN (PENDEKATAN PRAKTIS) - Puryatni, Anik; de Koning, Tom J. (Fakultas Kedokteran Universitas Brawijaya, 2008)
ABSTRACT Acute encephalopathy is a not a common, but a potential emergency situation in newborns and youngchildren. If the encephalopathy is not caused by asphyxia or infections of the brain, rare inborn errors ofmetabolism need to be considered. An acute encephalopathy due to an inborn error can occur in newborns,young infants, or even in childhood and is not always easily recognized because more subtle presentationscan occur. In this article we will give a practical guideline to the diagnostic approach of metabolic diseasespresenting with acute neurological symptoms with an emphasis on treatable disorders and the application indeveloping countries with limited diagnostic resources. The first step in the evaluation of patient with apossible metabolic disease is to categorise the clinical appearance of the patient in one of the followingclinical categories: Hypoglycemia phenotype; Intoxication phenotype; Neurotransmitter defect phenotype; andCellular energy metabolism defect phenotype. Second, combine this clinical classification with your physicaexamination and the result of routine laboratory investigations and this can lead to suspected diagnosis ofmetabolic disorders.Prompt recognition and treatment are important, because an acute metabolicencephalopathy can irreversible and interruption of normal neural activity in the developing brain can have along-lasting effect on psychomotor development. Delay in diagnosis and treatment may thus result in acutemetabolic decompensation, progressive neurologic injury, or even death. Key words: acute encephalopathy, inborn error metabolisme